Impact of maternal decision-making autonomy and self-reliance in accessing health care on childhood diarrhea and acute respiratory tract infections in Nepal. (September 2021) - Dev, R.; Williams-Nguyen, J.; Adhikari, S.P.; Dev, U.; Deo, S.; Hillan, E.
Abstract: Objective: This study aimed to examine the impact of maternal decision-making autonomy and self-reliance in accessing health care on childhood diarrhea and acute respiratory tract infection (ARI) in Nepal. Study design: This was a cross-sectional study. Methods: This study used data from the Nepal Demographic and Health Survey 2016. Mothers aged 15–49 years provided information about the health of 5308 children included in this analysis. Composite measures of maternal decision-making autonomy and self-reliance in accessing health care were used as exposure variables. Childhood diarrhea and ARI in the 2 weeks preceding the survey were primary outcome variables. Descriptive statistics and multivariable survey-weighted logistic regression methods were used in the analyses. Results: Maternal decision-making autonomy was high for approximately one-fourth (24.7%) of the children's mothers, and 81.7% of children's mothers reported self-reliance in accessing health care as a big problem. Diarrhea among children in the prior 2 weeks was reported among 8% (95% confidence interval [CI]: 6.9–8.4), whereas ARI was reported among 22% (95% CI: 21.1–23.5). The children of women who viewed a lack of self-reliance as a big problem had a 88% (adjusted odds ratio [aOR] = 1.88, 95% CI: 1.26–2.82, P  < 0.01) higher odds of diarrhea and 59% (aOR = 1.59, 95% CI: 1.29–1.95, P  < 0.001) higher odds of ARI compared with children of women who did not view self-reliance as a big problem. Conclusions: The study found a significant effect of maternal self-reliance in accessing health care on childhood diarrhea and ARI, independent of other sociodemographic factors. Improvement in maternal self-reliance in accessing health care of women is essential, particularly their autonomy with regard to healthcare seeking behavior and financial empowerment.